1986
DOI: 10.1002/cjce.5450640218
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic conversion of canola oil to fuels and chemical feedstocks Part I. Effect of process conditions on the performance of HZSM‐5 catalyst

Abstract: The conversion of canola oil to hydrocarbons using a shape selective zeolite catalyst is reported in this work. Canola oil was passed over HZSM‐5 catalyst in a fixed bed micro‐reactor and the effects of reaction temperature and oil space velocity on the conversion and selectivity were studied using a statistical experimental design. The results show that 60–95 wt% of the canola oil can be converted to hydrocarbons in the gasoline boiling range, light gases and water. The gasoline fraction contained 60–70 wt% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 8 publications
4
55
0
Order By: Relevance
“…Prasad et al performed a DOE on HZSM-5 catalyst in a fixed bed micro-reactor and results showed that 60-95 wt% of the canola oil can be converted to hydrocarbons in the gasoline boiling range, with 60-70 wt% aromatic hydrocarbons [14]. They subsequently added steam to the inlet and found a two-fold increase in catalyst life while keeping the same aromatic concentration in the liquid product [15].…”
Section: Introductionmentioning
confidence: 99%
“…Prasad et al performed a DOE on HZSM-5 catalyst in a fixed bed micro-reactor and results showed that 60-95 wt% of the canola oil can be converted to hydrocarbons in the gasoline boiling range, with 60-70 wt% aromatic hydrocarbons [14]. They subsequently added steam to the inlet and found a two-fold increase in catalyst life while keeping the same aromatic concentration in the liquid product [15].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the conversion of palm oil decreased as the reaction temperature increased. Catalytic conversion of canola oil was found to increase with an increase in reaction temperature, and decrease with an increase in space velocity (Prasad et al, 1986). It reached 96wt% conversion or complete conversion at 400°C with space velocity of 2 h-'.…”
Section: Resultsmentioning
confidence: 93%
“…In an earlier work [12][13][14][15][16][17], we studied the catalytic upgrading of cano1a oil over various acid catalysts such as HZSM-5, HY, H-mordenite, aluminum-pillared clays, silica-alumina and silico-alumino phosphates using a fixed-bed reactor in order to determine the effects on oil conversion and product distribution of catalyst characteristics such as acidity and acid site distribution, crystallinity, pore size and pore size distribution as well as to study the thermal stability of the catalyst under various operating environments. These studies showed that there were dramatic variations in both the overall oil conversion and yields of individual product for different catalysts used.…”
Section: Introductionmentioning
confidence: 93%
“…They were selected based on previous studies [12][13][14][15][16][17] in a fixed-bed reactor which showed that the product distributions obtained with these three catalysts were widely different.…”
Section: Catalyst Preparation and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation